(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2013)
The research work carried out shows the utility of brinell hardness for evaluating the rock strength . Tests were carried out on samples obtained from Hassi Messaoud OMN602 and OMN402 wells , at different depths ,rangings from 1900m to 2900m. It is well known the brinell hardness in mechanical engineering, can be used on rocks in the same way as that of metals. Useful emperical relations between brinell hardness and the strength properties of the rock were obtained.